The electrochemical properties of Sr(Ti,Fe)O3-δ for anodes in solid oxide fuel cells - Nenning, Andreas; Volgger, Lukas; Miller, Elizabeth; Mogni, Liliana Verónica; Barnett, Scott; Fleig, Jürgen (Electrochemical Society, 2017)
Fil: Nenning, Andreas. ETH Zurich; Suiza